Transiently impaired endothelial function during thyroid hormone withdrawal in differentiated thyroid cancer patients - Hou, Li-ying; Li, Xiao; Zhang, Guo-qiang; Xi, Chuang; Shen, Chen-tian; Song, Hong-jun; Bai, Wen-kun; Qiu, Zhong-ling; Luo, Quan-yong (Frontiers in Endocrinology, 2023)
Purpose Endothelial dysfunction, which was associated with chronic hypothyroidism, was an early event in atherosclerosis. Whether short-term hypothyroidism following thyroxine withdrawal during radioiodine (RAI) therapy was associated with endothelial dysfunction in patients with differentiated thyroid cancer (DTC) was unclear. Aim of the study was to assess whether short-term hypothyroidism could impair endothelial function and the accompanied metabolic changes in the whole process of RAI therapy. Methods We recruited fifty-one patients who underwent total thyroidectomy surgery and would accept RAI therapy for DTC. We analyzed thyroid function, endothelial function and serum lipids levels of the patients at three time points: the day before thyroxine withdrawal(P1), the day before 131I administration(P2) and 4-6 weeks after RAI therapy(P3). A high-resolution ultrasound named flow-mediated dilation (FMD) was used to measure endothelial function of the patients. Results We analyzed the changes of FMD, thyroid function and lipids at three time points. FMD(P2) decreased significantly compared to FMD(P1) (P1vsP2, 8.05 ± 1.55vs 7.26 ± 1.50, p<0.001). There was no significant difference between FMD(P3) and FMD(P1) after restoring TSH (thyroid stimulating hormone) suppression therapy (P1 vs P3, 8.05 ± 1.55 vs 7.79 ± 1.38, p=0.146). Among all parameters, the change of low-density lipoprotein (ΔLDL) was the only factor correlated negatively with the change of FMD (ΔFMD) throughout the RAI therapy process (P1-2, r=-0.326, p=0.020; P2-3, r=-0.306, p=0.029). Conclusion Endothelial function was transiently impaired in DTC patients at short-term hypothyroidism state during the RAI therapy, and immediately returned to the initial state after restoring TSH suppression therapy.